NOVEL GADIS PANTAI KARYA PRAMOEDYA ANANTA TOER: ANALISIS HEGEMONI *) (A Novel Gadis Pantai by Pramoedya Ananta Toer: an Hegemony Analysis) - Muzakka, Moh (Balai Bahasa Jawa Tengah, 2017)
A literary work used by author in offering some ideologies to the readers. Through this literary work, especially the conflict between characters, an author can influence reader?s view and ideology. This article tends to explore ideology contention of the novel Gadis Pantai by Pramoedya Ananta Toer used Gramsci hegemony analysis. The result of this analysis is novel Gadis Pantai offers three ideologies: feudalism, coast cultural primitive, and socialist realism. In this novel, the two contrast cultures viewed as a quiet enough culture so that the ideal culture is socialist realism. Keywords: ideology, coast, gentry, hegemony, socialist realism.